Burden of headache in a HIV-positive population of sub-Saharan Africa. (August 2022) - Leone, Massimo; Giani, Luca; Phaka, Monica; Uluduz, Derya; Tayyar, Şaşmaz; Kamponda, Maureen; Tolno, Victor Tamba; Guidotti, Giovanni; Marazzi, Maria Cristina; Steiner, Timothy J
Background: About 26 million people are living with HIV in sub-Saharan Africa. The DREAM programme in sub-Saharan Africa provides free healthcare for HIV/AIDS and a range of chronic non-communicable diseases. HIV is a risk factor for neurological non-communicable diseases including stroke and epilepsy, which themselves are associated with headache, and HIV may be a direct risk factor for headache. We investigated the prevalence and burden of headache in a HIV+ population in sub-Saharan Africa. Methods: At the DREAM Centre in Blantyre, Malawi, a low-income country with a population of 19 million and 9.2% HIV prevalence, a structured questionnaire was administered by a trained lay interviewer to consecutively attending HIV+ patients aged 6–65 years. All were monitored with regular viral load detection. Results: Of 513 eligible patients invited, 498 were included (mean age 34.1 ± 12.8 years; 72% females; 15 declined). All were on antiretroviral treatment, with viral load undetectable in 83.9%. The 1-year prevalence of headache was 80.3% (females 83.6%, males 71.9%); 3.8% had ≥15 headache days/month, 1.4% had probable medication-overuse headache. Mean overall headache frequency was 4.4 ± 5.4 days/month. Those reporting headache lost means of 2.3% of paid workdays and 3.3% of household workdays because of headache. Only one third had sought advice for their headache. Conclusions: Headache is very prevalent among HIV+ patients in Malawi, imposing additional burden and costs on individuals and the community. Management of headache disorders should be implemented in HIV centres, as it is for other chronic non-communicable diseases.